SENHORA SANT’ANA E DIVINO ESPÍRITO SANTO: Festa de Correntes no Terreiro Fé em Deus - AIRES, Maria do Socorro Rodrigues de Souza (2025)
This research has as a background the religion of the drum of Mina, in Terreiro Fé em Deus in São Luís do Maranhão, taking into account its symbolic influence in the context of the Feast of Lady Sant'Ana and Divine Holy Spirit. From a theoretical framework of anthropological and sociological studies of religion and culture, in this research, I try to elaborate an ethnography that makes it possible to understand how the "world view" of the subjects responsible for the organization and realization of the party is processed, focusing on the performance of Dina, Rôxa and the group of Nine, analyzing the ritual objects of the party, the practices of these subjects and their symbolic performances. Thus, the research seeks to point out how this festival is carried out, which has a specific organization and, in fact, is guided by the terreiro's belief system, with reference to the spiritual entities that are in evidence in the theme of the festival, or as they say in the terreiro: “who is reigning”. With this analysis, I intend to demonstrate that people act in relation to things, according to the meaning that these things have for them, as well as, they elaborate meanings that give meaning to their actions, social interactions and the force that these meanings exert, in the form of symbols, provide the repertoire by which we create culture, or the modes of thought, feeling and action that characterize our society and everything that happens around us.